Perimedullary arteriovenous fistulas of the craniovertebral junction: A systematic review - Umana, Giuseppe Emmanuele (J Craniovertebr Junction Spine, 2020)
Perimedullary arteriovenous fistulas (PMAVFs) are uncommon vascular malformations, and they rarely occur at the level of the craniovertebral junction (CVJ). The therapeutic management is challenging and can include observation alone, endovascular occlusion, or surgical exclusion, depending on both patient and malformation characteristics. A systematic literature search was conducted using MEDLINE, Scopus, and Google Scholar databases, searching for the following combined MeSH terms: (perimedullary arteriovenous fistula OR dural arteriovenous shunt) AND (craniocervical junction OR craniovertebral junction). We also present an emblematic case of PMAVF at the level of the craniovertebral junction associated to a venous pseudoaneurysm. A total of 31 published studies were identified; 10 were rejected from our review because they did not match our inclusion criteria. Our case was not included in the systematic review. We selected 21 studies for this systematic review with a total of 58 patients, including 20 females (34.5%) and 38 males (65.5%), with a female/male ratio of 1:1.9. Thirty-nine out of 58 patients underwent surgical treatment (67.2%), 15 out of 58 patients were treated with endovascular approach (25.8%), 3 out of 58 patients underwent combined treatment (5.2%), and only 1 patient was managed conservatively (1.7%). An improved outcome was reported in 94.8% of cases (55 out of 58 patients), whereas 3 out of 58 patients (5.2%) were moderately disabled after surgery and endovascular treatment. In literature, hemorrhagic presentation is reported as the most common onset (subarachnoid hemorrhage in 63% and intramedullary hemorrhage in 10%), frequently caused either by venous dilation, due to an ascending drainage pathway into an intracranial vein, or by the higher venous flow rates that can be associated with intracranial drainage. Hiramatsu and Sato stated that arterial feeders from the anterior spinal artery (ASA) and aneurysmal dilations are associated with hemorrhagic presentation. In agreement with the classification by Hiramatsu, we defined the PMAVF of the CVJ as a vascular lesion fed by the radiculomeningeal arteries from the vertebral artery and the spinal pial arteries from the ASA and/or lateral spinal artery. Considering the anatomical characteristics, we referred to our patient as affected by PMAVF, even if it was difficult to precisely localize the arteriovenous shunts because of the complex angioarchitecture of the fine feeding arteries and draining veins, but we presumed that the shunt was located in the point of major difference in vessel size between the feeding arteries and draining veins. PMAVFs of CVJ are rare pathologies of challenging management. The best diagnostic workup and treatment are still controversial: more studies are needed to compare different therapeutic strategies concerning both long-term occlusion rates and outcomes.